Correlation between anti-hypertensive drugs and disease progression among moderate, severe, and critically ill COVID-19 patients in the second referral hospital in Surbaya: A retrospective cohort study - Satriyo Dwi Suryantoro, - (Taylor & Francis, 2021)
Background: Hypertension, as the comorbidity accompanying COVID-19, is related to angiotensin-converting enzyme 2 receptor (ACE-2R) and endothelial dysregulation which have an important role in blood pressure regulation. Other anti-hypertensive agents are believed to trigger the hyperinflammation process. We aimed to figure out the association between the use of anti-hypertensive drugs and the disease progression of COVID-19 patients. Methods: This study is an observational cohort study among COVID-19 adult patients from moderate to critically ill admitted to Universitas Airlangga Hospital (UAH) Surabaya with history of hypertension and receiving anti-hypertensive drugs. Results: Patients receiving beta blockers only had a longer length of stay than angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ACEI/ARB) or calcium channel blockers alone (17, 13.36, and 13.73 respectively), had the higher rate of intensive care unit (ICU) admission than ACEi/ARB (p 0.04), and had the highest mortality rate (54.55%). There were no significant differences in length of stay, ICU admission, mortality rate, and days of death among the single, double, and triple anti-hypertensive groups. The mortality rate in groups taking ACEi/ARB was lower than other combination. Conclusions: Hypertension can increase the severity of COVID-19. The use of ACEI/ARBs in ACE-2 receptor regulation which is thought to aggravate the condition of COVID-19 patients has not yet been proven. This is consistent with findings in other anti-hypertensive groups.